Towards a typology of agri-urban patterns to support spatial planning: evidence from Lisbon, Portugal - Abrantes, Patrícia (2022)
Urbanisation in Europe has been the main cause of agricultural land fragmentation and agricultural land use loss and has given rise to significant socio-economic and environmental costs, particularly in urban regions. Accordingly, there is a consensus in the literature that sustaining urban and peri-urban agriculture are significant towards urban sustainable development. This paper aims to characterise agri-urban spatial patterns and changes occurring in the Lisbon metropolitan region (LMR) by using indicators from both urban and agricultural dimensions. A self-organising map (SOM) clustering method was used to build an agri-urban classification. Nine clusters were proposed. We found that in the LMR, urban and agriculture patterns are diverse: agriculture can range from gardening to intensive and extensive forms; and from decline to stability. We discuss that the use of multidimensional indicators enables comprehensive typologies and allows for a better territorial diagnosis that can contribute to informing decision-makers towards more effective protection of agriculture in spatial planning.